Mixed-Signal Parallel Compressive Spectrum Sensing for Cognitive Radios - Zhuizhuan Yu; Xi Chen; Sebastian Hoyos; Brian M. Sadler; Jingxuan Gong; Chengliang Qian (International Journal of Digital Multimedia Broadcasting)
Wideband spectrum sensing for cognitive radios requires very demanding analog-to-digital conversion (ADC) speed and dynamic range. In this paper, a mixed-signal parallel compressive sensing architecture is developed to realize wideband spectrum sensing for cognitive radios at sub-Nqyuist rates by exploiting the sparsity in current frequency usage. Overlapping windowed integrators are used for analog basis expansion, that provides flexible filter nulls for clock leakage spur rejection. A low-speed experimental system, built with off-the-shelf components, is presented. The impact of circuit nonidealities is considered in detail, providing insight for a future integrated circuit implementation.